Analogue Behavioral Modeling of GTO. (26th July 2011) - Azzouz, Y.; Schneider, H.; Coyitangiye, L.-A.; Ravelo, B.
Abstract : An analog behavioral model of high power gate turn-off thyristor (GTO) is developed in this paper. The fundamental methodology for the modeling of this power electronic circuit is based on the use of the realistic diode consideration of non-linear junctions. This modeling technique enables to perform different simulations taking into account the turn-on and turn-off transient behaviors in real-time. The equivalent circuits were simulated with analog software developed in our laboratory. It was shown that the tested simple and compact model allows the generation of accurate physical characteristics of power thyristors under dynamic conditions. The model understudy was validated with analog simulations based on operational amplifier devices.